Re: Quadratic Equation
Skyshr wrote:f(x) = ax^2 + bx + c
where a, b, c are real and a is not equal to zero
If d, e are the roots of f(x) - x = 0,
how to prove d, e are also the roots of f[f(x)] - x = 0?
This looks a bit wrongly stated to me, because we are given
f(x) = ax^2 + bx + c and
f(x) - x = 0 or stated otherwise f(x) = x, implying a = 0, b = 1 and c = 0, a contradiction!
So if f(x) equals x of course f[f(x)] - x = 0 because f(x) = x so f(f(f(f(x)))) = x so f(f(x)) - x must equal 0.
Knowledge of the roots D and E is superflous when the question is stated so!
The only correct way of asking what you meant would be to say
f(x) = ax^2 + bx + c where a, b, c are real and a is not equal to zero
If d, e are the roots of f(x) - x, prove d, e are also the roots of f[f(x)] - x
* * *
Adding the = 0 as you did technically introduced a contradiction that a was not equal to zero!